تأثير معدلات مختلفة من الأسمدة الآزوتية في نمو أشجار السفرجل حديثة السن - خربوتلي رشيد (Latakia University Journal -Biological Sciences Series, 2019)
بهدف تحديد الكمية المناسبة من الأسمدة الآزوتية اللازمة لنمو أشجار السفرجل حديثة السن، استخدمت عدة معاملات سمادية ، وأظهرت الدراسة على أشجار السفرجل من الصنف الصيداوي والمطعمة على الأصل البري للسفرجل النتائج التالية : 1- أظهرت إضافة الأسمدة الآزوتية لأشجار السفرجل حديثة السن دوراً كبيراً وتأثيراً فعالاً في النمو الخضري لهذه الأشجار مقارنة مع أشجار الشاهد . 2- إن النمو الطولي للنموات الخضرية الحديثة يظهر بشكل واضح في شهر تموز في حين أن النمو العرضي لمحيط ساق الشجرة وقطر قاعدة النموات الحديثة يظهر جلياً في شهر أيلول. 3- أعطت المعاملة السمادية الرابعة (بمعدل 100غ آزوت نقي للشجرة ) أفضل النتائج للعلاقة بين مقدار النمو وكمية الأسمدة. In order to determine the suitable Treatment of Nitrogen fertilizer for the best growth of young quince Trees . Many different fertilizer Treatments have been tested on quince Trees variety Sedawi grafted on wild quince stock, and the study showed the following result . 1- The addition of Nitrogen fertilizer to young quince Trees showed an efficient roll and impact on the foliargrowth of treated Trees in comparison with non Treated Trees (control ) . 2- The longitudial growth of New green shoots was obvious on July, whereas the cross-seetional growth of tree stem and the diameter of new shoots base were obvious on September . 3- The best results of the correlation between growth ratio and the amount of added fertilizer was obtained when the Fourth fertilizer treatment (100g N / Tree) was used.